2000
DOI: 10.1074/jbc.275.3.1887
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Multidrug Resistance P-glycoprotein via Nuclear Factor-κB Activation Protects Kidney Proximal Tubule Cells from Cadmium- and Reactive Oxygen Species-induced Apoptosis

Abstract: Cadmium-mediated toxicity of cultured proximal tubule (PT) cells is associated with increased production of reactive oxygen species (ROS) and apoptosis. We found that cadmium-dependent apoptosis (Hoechst 33342 and annexin V assays) decreased with prolonged CdCl 2 (10 M) application (controls: 2.4 ؎ 1.6%; 5 h: ؉5.1 ؎ 2.3%, 20 h: ؉5.7 ؎ 2.5%, 48 h: ؉3.3 ؎ 1.0% and 72 h: ؉2.1 ؎ 0.4% above controls), while cell proliferation was not affected. Reduction of apoptosis correlated with a time-dependent up-regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
235
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(254 citation statements)
references
References 52 publications
15
235
2
Order By: Relevance
“…Therefore, the resistant phenotype of cancer cells associated with constitutive or induced NF-kB activity has been associated with NF-kBdependent expression of proteins inhibiting the various proapoptotic pathways (Barkett and Gilmore, 1999;Bours et al, 2000). Our present data as well as a recent publication (Kuo et al, 2002) indicate that NF-kB also acts upstream by controlling drug efflux through P-gp expression in cancer cells while previous reports had demonstrated the NF-kB-dependent regulation of P-gp expression in renal tubules or liver which physiologically express the protein (Thevenod et al, 2000;Ros et al, 2001). Therefore, it is likely that increased P-gp expression participates in NF-kB-related cancer cell resistance to treatment.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Therefore, the resistant phenotype of cancer cells associated with constitutive or induced NF-kB activity has been associated with NF-kBdependent expression of proteins inhibiting the various proapoptotic pathways (Barkett and Gilmore, 1999;Bours et al, 2000). Our present data as well as a recent publication (Kuo et al, 2002) indicate that NF-kB also acts upstream by controlling drug efflux through P-gp expression in cancer cells while previous reports had demonstrated the NF-kB-dependent regulation of P-gp expression in renal tubules or liver which physiologically express the protein (Thevenod et al, 2000;Ros et al, 2001). Therefore, it is likely that increased P-gp expression participates in NF-kB-related cancer cell resistance to treatment.…”
Section: Discussioncontrasting
confidence: 50%
“…Ogretmen et al demonstrated that a protein complex consisting of NF-kB /p65 and c-Fos transcription factors interacts with the CAAT promoter region in MCF7 cells and negatively regulates the human mdr1 promoter activity (Ogretmen and Safa, 1999). It has also been reported that an insulin-induced mdr1 expression is mediated by NF-kB in rat hepatoma cells (Zhou and Kuo, 1997) and that NF-kB can protect kidney proximal tubule cells from cadmium and oxidative stress by increasing P-gp expression (Thevenod et al, 2000). Recent papers reported that NF-kB was involved in TNF-a-induced mdr1 expression in hepatocytes, in 2-acetylaminofluorene-induced MDR expression in liver cells and in constitutive MDR expression in drug-resistant cells (Ros et al, 2001;Um et al, 2001;Kuo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As mdr1b is the more primitive of the mdr1 genes (as determined by phylogenetic analysis (Growtree) (Furuya et al, 1997a)), one interpretation of the current studies is that increased mdr1b decreases cell survival in a p53 and mdr1b dependent fashion. This idea is circumstantially supported by studies showing mdr1b is readily upregulated by cytotoxic agents that are, for the most part, not mdr1 substrates (e.g., 3-methylcholanthracene, a¯atoxinB1, methylmethanesulfonate, mitoxantrone or reactive oxygen (Fardel et al, 1998;Ziemann et al, 1999;Thevenod et al, 2000)) and mdr1b is transcriptionally upregulated in cells undergoing cell death (Schrenk et al, 1996). However, given that di erent levels of p53 are linked to di erent cellular outcomes, i.e., low levels of p53 arrest cell growth and high levels induce apoptosis (Levine, 1997); mdr1b's role in apoptosis may be dramatically in¯uenced by the cell context.…”
Section: Discussionmentioning
confidence: 59%
“…The basis for the switch is a presumed transcriptional upregulation of mdr1a. Although, the mechanism accounting for this conversion is unknown, it may be hypothesized that high levels of mdr1b are deleterious to cell survival, a concept that is consistent with studies showing that cytotoxic drugs that are not mdr1 substrates as well as oxidative stress induce mdr1b (Ziemann et al, 1999;Thevenod et al, 2000) and that transcriptional upregulation of mdr1b has been correlated with decreased viability (Schrenk et al, 1996).…”
Section: Introductionmentioning
confidence: 52%
“…PS is normally located on the cytoplasmic inner surface of the membrane. However, in the case of apoptosis PS is translocated to the outer leaflet of the membrane and can be detected by extracellular annexin V [22].…”
Section: Imaging and Nanoprocessing Methodsmentioning
confidence: 99%